Acute Enterovirus Encephalitis as a Cause for Isolated Visual and Auditory Hallucinations in a 22-Year-Old Patient. (23rd April 2021) - Deest, M.; Eberlein, C.; Bleich, S.; Frieling, H.; Skripuletz, T.; Neyazi, A.
Abstract : Viral encephalitis often presents with severe illness, headache, fever, behavioral changes, altered level of consciousness, and focal neurologic deficits. One of the most feared kind of virus encephalitis is herpes simplex encephalitis; however, other central virus infections are also capable of presenting with psychiatric symptoms. Here, we report the case of a 22-year-old woman with first time visual and auditory hallucinations due to an acute enterovirus encephalitis with no cerebrospinal fluid abnormalities but a positive PCR result for enterovirus (ECHO). During treatment, the symptoms deteriorated, and she hat to be shifted to the sheltered ward because of imperative suicidal auditory hallucinations. Under treatment with risperidone and olanzapine, symptoms suddenly stopped and did not reoccur under subsequent reduction of the antipsychotic medication.